Intellectual capital reporting - Chase, Rory L. (Rory Lee), 1950- (Journal of intellectual capital, 2007)
One of the most active areas of intellectual capital study is IC measurement and reporting. Research ranges from developing IC frameworks and guidelines to market effectiveness and efficiency in the IC disclosure process. In this e-book, leading academics and practitioners provide insights into current research and trends in IC assets reporting.